Rancang Bangun Aplikasi Pengolahan Data Bank Sampah Berbasis Web (Studi kasus Pada Rungkut Lor GG.III RT.03 RW.06) - Yuliantoro, Anang; Wurijanto, Tutut; Binawati, lilis (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
Garbage Bank in Rungkut Lor Gg. III RT. 03 RW.06 Surabaya is an environmental group engaged in environmental health, this activity is carried out by community representatives, and its customers are also local RT community. The garbage bank Rungkut lor Gg. III RT. 03 RW. 06 is carried out once a month in the RW hall to weigh the garbage. The people resulting from the weighing of the residents are only recorded in the passbook and the residents' savings cannot be taken directly. For taking citizens' savings, it can only be done once a year. When taking citizens' savings, the total amount of savings is for 1 year. In processing the bank's trash data, it is still written manually with a document filing system that is not neat and the writing is not clear, finally the data is tucked and lost. So that to find the data needed a long time, it felt less effective and inefficient. Based on the description of the above problems, a web-based garbage bank data processing application was built. This application replaces the process of recording junk data and data of residents who still use books, increase security in the information of citizens' savings, make it easier for residents to see citizens' savings, as well as help waste bank managers in managing the recording of citizens' data and knowing the history of the sale of people's waste and the total proceeds of selling garbage citizens every year.